Literatur Review Meta Analitik Hubungan Lama Duduk dengan Low Back Pain (LBP) - Ayu Lestari; Imran Safei; Lisa Yuniarti (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Low back pain (LBP) is one of the most common musculoskeletal complaints globally and is the main cause of decreased work productivity. One of the risk factors that has been widely studied in the literature is prolonged sitting duration. Prolonged sitting activities cause increased static pressure on the lumbar spine, fatigue of the supporting muscles, as well as a decrease in local blood flow that can trigger chronic pain. This study is a literature review with a meta-analytical approach that aims to analyze the relationship between long-term sitting and the incidence of LBP. The review process was carried out following PRISMA guidelines through searches on PubMed, Scopus, ScienceDirect, and Google Scholar databases for publication in 2020–2025. Of the 20 previous studies analyzed, most showed a positive association between sitting time and an increased risk of LBP, both in adults, adolescents, and children. Sitting for more than 6 hours per day increases the risk of LBP by 33%, especially in individuals with low physical activity. In addition, longer sitting durations with poor posture and minimal active rest were found in the group of office workers and professional drivers who had a high prevalence of LBP. Physical activity has been shown to play a protective role against the risk of LBP, while ergonomic interventions such as lumbar support can reduce pain complaints. Although most studies were observational, the consistency of results supports the importance of prevention through reduced sitting time, increased physical activity, and ergonomic work environment settings. These findings provide a scientific basis for multidimensional interventions to effectively reduce the incidence of LBP.